Pelatihan Perhitungan Harga Pokok Produksi (HPP) dalam Menentukan Harga Jual Fried Chicken - Farida Farida; Endang Wulandari; Dewi Gita Kartika (LPPM IT Telkom Purwokerto, 2024)
MSMEs play an important role in business development and national economic progress at large. One type of MSME that is mushrooming at the moment is a culinary business that serves fried chicken menus or more specifically fried chicken menus. The strategy for determining product prices or selling prices is of course one that can determine victory in the business competition where many culinary-type businesses are currently emerging. Haji Tan, as the owner of a fried chicken business, wants to know the calculation and determination of the Cost of Production so that he can review the selling price of his product which has been set to adapt to the economic conditions of the community and nation due to the increase in prices of basic necessities. The current price determination for Haji Tan's Fried Chicken business products is based on similarities with competitors or mere estimates. With this community service, the aim is to explain that Kentucky chicken must be sold based on the calculation of the cost of production in order to revise the selling price of the product which will be applied in Haji Tan's business branches and will later get a stable profit. This service carries out training activities using counseling/socialization and practical methods. The implementation of training activities has run smoothly and well so that it can provide benefits in increasing participants' knowledge and skills. Currently, participants can adjust the calculation of the cost of production (HPP )to determine the selling price. Partners have been able to correctly prepare the cost of production so they can estimate the profits they will make and determine their product sales targets.